(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Jhum cultivation (Shifting cultivation) has been practising from the very beginning of human civilization. Today, it is also practised traditionally generally in hilly region. It is a curse to the human existence because of creating so many problems such as environmental, soil erosion, soil fertility, loss of flora and fauna, loss of water resources, etc. This paper seeks to examine an in-depth study to solve the problems created by the shifting cultivation in the country in general and in Arunachal Pradesh in particular as to bring sustainable development by solving the problems created by Shifting Cultivation.